EXCESSIVE SECRECY IN DEMOCRACIES: BUREAUCRATIC REFLEX OR SECURITY ILLUSION? - Matić, Goran (The Policy of National Security, 2026)
Systematic excessive classification of information within the security apparatuses of the United States, the European Union, and key NATO allies constitutes a structural anomaly within liberal democracies. Through comparative analysis, the article identifies that the principal driver of this phenomenon is the distinction between security secrecy (the protection of genuine security capabilities) and political secrecy (the protection of institutions from accountability). The research demonstrates that, despite different legal traditions, all examined systems share common structural patterns: defensive classification as a risk-minimization strategy, asymmetric incentives that penalize openness, and weak mechanisms of external oversight. The consequences of such practices include erosion of public trust, constrained cooperation within alliances, and reduced effectiveness in decision-making processes. The article concludes that solutions require a paradigm shift – from the logic of the need to conceal toward the principle of the right to know, grounded in the presumption of openness as the basis of democratic legitimacy. Key operational steps include the introduction of mandatory sunset clauses, strengthening the independence and competences of oversight bodies, and harmonizing standards at NATO and European Union levels to prevent misuse of secrecy for information management rather than security protection.